Panic, Don't Panic: Poetry and Affective Politics from the Cold War to Trump. - Beardsworth, Adam (Canadian Review of American Studies)
In both the Cold War and the Trump era, the fear of future threat has provided politicians with a carte blanche for generating anxiety among American citizens. This essay examines how poets in each era responded to the political cultivation of private insecurity, a practice that proliferates the fear, the anxiety, and the weariness that are grounded in the possibility of future threat. For many poets of both the Cold War and Trump eras, political critique lies not in the desire to express rational opposition to irrational policies but in the ability to make tangible the affective consequences of the cultivation of national insecurity.